Corporate Income Taxes under Pressure : Why Reform Is Needed and How It Could Be Designed - Mooij, Ruud A. (International Monetary Fund, 2021)
The book describes the difficulties of the current international corporate income tax system. It starts by describing its origins and how changes, such as the development of multinational enterprises and digitalization have created fundamental problems, not foreseen at its inception. These include tax competition-as governments try to attract tax bases through low tax rates or incentives, and profit shifting, as companies avoid tax by reporting profits in jurisdictions with lower tax rates. The book then discusses solutions, including both evolutionary changes to the current system and fundamental reform options. It covers both reform efforts already under way, for example under the Inclusive Framework at the OECD, and potential radical reform ideas developed by academics.